The Influence of Leadership Style, Work Discipline and Work Motivation on Employee Performance at the Rawa Shop, Gianyar Regency - Sukriana, I Wayan Gede Agus; Goca, I Gusti Putu Agung Widya (Baca Dulu Publisher, 2024)
This study aims to determine the effect of leadership style, work discipline and work motivation on employee performance at the Rawa Shop, Gianyar Regency. The analytical tool used to test the hypothesis is multiple linear regression analysis. Based on the results of the analysis shows that the Leadership Style has a positive and significant effect on employee performance. This means that the better the Leadership Style, the better the employee's performance will be. Similarly, Work Discipline has a positive and significant effect on employee performance, meaning that if Work Discipline is improved then employee performance will increase and the same is true for Work Motivation and it has a positive and significant effect on employee performance, meaning that if Work Motivation is getting better, employee performance will be better.